2014
DOI: 10.1002/pros.22776
|View full text |Cite
|
Sign up to set email alerts
|

A ROS/STAT3/HIF-1α signaling cascade mediates EGF-induced TWIST1 expression and prostate cancer cell invasion

Abstract: We demonstrate a mechanism by which EGF promotes prostate cancer cell progression through a ROS/STAT3/HIF-1α/TWIST1/N-cadherin signaling cascade, providing novel biomarkers and promising therapeutic targets for prostate cancer cell progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 30 publications
1
51
0
Order By: Relevance
“…Although we have previously reported the constitutive activation of HIF-1α in normoxic cancer cells with a stable MDR phenotype [30], the parallel increase in HIF-1α transcription and the progressive acquisition of MDR is a new observation. This trend may be due to the use of doxorubicin as selective agent: indeed, in normoxia the drug produces reactive oxygen species [31] that increase HIF-1α [32]. During the onset of the MDR phenotype, the increase of HIF-1α was paralleled by an increase of CAXII and Pgp mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have previously reported the constitutive activation of HIF-1α in normoxic cancer cells with a stable MDR phenotype [30], the parallel increase in HIF-1α transcription and the progressive acquisition of MDR is a new observation. This trend may be due to the use of doxorubicin as selective agent: indeed, in normoxia the drug produces reactive oxygen species [31] that increase HIF-1α [32]. During the onset of the MDR phenotype, the increase of HIF-1α was paralleled by an increase of CAXII and Pgp mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence have demonstrated that EGF can induce EMT in various types of cancer cells, including breast cancer [30], prostate cancer [31, 32], cervical cancer [33], and head and neck cancer [22, 34]. Meanwhile, EGF stimulation endows head and neck cancer cells with stem-like cell properties [22].…”
Section: Introductionmentioning
confidence: 99%
“…Cell migration is a dynamic, wellorganized and complex process requiring co-ordination of many molecules in cells. Numerous studies have demonstrated that EGF activates its receptor, following resulting in increased cell migration in human tumorous cells (Cho et al, 2014;Jeong et al, 2014;Magi et al, 2014), thus EGF, via its receptor, plays an important role in cell migration and tumor invasion. Our research, using in vitro wound healing assay, clearly showed that EGF induced human cervical cancer SiHa cell migration (Figure 1).…”
Section: Discussionmentioning
confidence: 99%